Methylations in dilated cardiomyopathy and heart failure - Qin, Cong; Qin, Yansong; Zhou, Shanshan (Frontiers in Cardiovascular Medicine, 2025)
Dilated cardiomyopathy (DCM) is characterized by impaired expansion or contraction of the left or both ventricles in the absence of abnormal load conditions (such as primary valve disease) or severe coronary artery disease that can lead to ventricular remodeling. Genetic mutations, infections, inflammation, autoimmune diseases, exposure to toxins, and endocrine or neuromuscular factors have all been implicated in the causation of DCM. Cardiomyopathy, particularly DCM, often has genetic underpinnings, with established or suspected genetic origins. Up to 40% of DCM cases involve probable or confirmed genetic variations. The significance of RNA modification in the pathogenesis of hypertension, cardiac hypertrophy, and atherosclerosis is well-established. Of late, RNA methylation has garnered attention for its involvement in DCM. This review examines the biological mechanisms and effects of RNA methylation in DCM and heart failure.